SUPEROUTBURST OF V1504 CYGNI IN 2003 - Antonyuk, O. I. (Одеські астрономічні публікації, 2017)
The photometry of the SU UMa-type dwarf nova V1504 Cygni during the superoutburst is performed. The star displayed the superoutburst decay at a rate about 0.15 mag / day. Evolution of super-humps during the superoutbursts is discussed.